The Impact of the Social Capital on the Resilience of a Manufacturing Supply Chains: The Mediating Role of Agility of a Supply Chain and the Moderating Role of Absorptive Capacity of Supply Chains - Wallop Piriyawatthana (International Journal of Supply Chain Management, 2020)
The present study contributes to the SCM and marketing literature, concerning the roles of SCM alignment and firm’s absorptive capacity to utilize social capital for achieving supply chain resilience. Firstly, understanding means to enhance supply chain resilience via social capital, therefore, in this regard taking absorptive capacity into account is necessary. Secondly, this study highlights that SCM alignment has the power to restrict the extent that social capital supports the firm’s absorptive capacity. Thirdly, the study has examined the moderating role of supply chain agility in the relationship between the social capital and supply chain resilience. Finally, the supply chain resilience outcomes were examined. As a result, those conditions and means were also explained through which firms utilize accumulated external resources in the form of social capital and achieve supply chain resilience to enhance organizational performance.  The study has used the SEM-PLS for the analysis of the data. The response rate of the current study is 75.1 percent. The data is collected from the manufacturing firms listed in Indonesian stock exchange. The results of the study highlight that firms mostly possess valuable resources that are entrenched within inter-organizational ties, and a few such resources may remain inactive if not utilized against adversities and risks. Hence, absorptive capacity must be developed and activated by the firms to capitalize social capital in an effort to develop supply chain resilience.